2021
DOI: 10.3390/jcm10102091
|View full text |Cite
|
Sign up to set email alerts
|

What Is New in Helicobacter pylori Diagnosis. An Overview

Abstract: Helicobacter pylori infection remains one of the most prevalent infections worldwide, especially in low-resource countries, and the major risk factor for peptic ulcer and gastric cancer. The “test-and-treat” strategy is recommended by several guidelines and consensus. The choice of testing method is based on patient age, presence of alarm signs and/or symptoms, use of non-steroidal anti-inflammatory drugs, as well as local availability, test reliability, and cost. Culture is the gold standard to detect H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 120 publications
2
51
0
3
Order By: Relevance
“…The PCR technique is being developed to investigate the presence of microorganism directly from the clinical samples. Compared with conventional PCR, real-time PCR has several advantages, such as short working time, high specificity and low risk of contamination [ 8 , 35 ]. Quantitative results from real-time PCR in our study showed that the sensitivity and specificity were 100% and 100% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR technique is being developed to investigate the presence of microorganism directly from the clinical samples. Compared with conventional PCR, real-time PCR has several advantages, such as short working time, high specificity and low risk of contamination [ 8 , 35 ]. Quantitative results from real-time PCR in our study showed that the sensitivity and specificity were 100% and 100% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with achlorhydria, recent gastroduodenal hemorrhage, or usage of proton pump inhibitors (PPIs), antibiotics, H2-receptor antagonists, bismuth-containing substance, or severe atrophy and intestinal metaplasia are at risk of false-negative results [ 54 ]. To reduce false-negative results, it is recommended that these medicines be avoided before RUT (two weeks for PPIs and 4 weeks for antibiotics).…”
Section: Current Diagnostic Methodsmentioning
confidence: 99%
“…In current practice, when there is a clear indication for digestive endoscopy, without contraindications for taking biopsies, the rapid urease test has the first-line indication to testing for diagnosis. To maximize the sensitivity of RUTs, the current recommendation recommends obtaining at least two biopsy specimens from the stomach body and the antrum if gastroscopy is conducted [ 54 , 55 ]. In a study conducted by Lee and colleagues in patients with peptic ulcer bleeding, the sensitivity of RUT was raised by increasing the number of biopsies taken from both the antrum and the corpus [ 56 ].…”
Section: Current Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] There are several experimented molecular-based diagnostic kits for detection of H pylori and its antibiotic resistance The molecular test have several advantages to conventional culture and culture-based antibiotic susceptibility tests. [7] GenoTypeHelicoDR (Hain Lifescience, Nehren, Germany) is a rapid molecular test for simultaneous detection of H pylori and its resistance to clarithromycin and quinolone based on DNA strip technology. Test including multiplex polymerase chain reaction amplification with subsequent reverse hybridization step.…”
Section: Introductionmentioning
confidence: 99%